PENCARIAN ARTI AYAT AL-QUR’AN DENGAN SPEECH RECOGNITION MENGGUNAKAN ALGORITMA BERRY RAVINDRAN BERBASIS ANDROID - Hafizah Safwani; Suendri Suendri; Triase Triase (JISTech (Journal of Islamic Science and Technology), 2021)
Students in grades 4-5 Elementary School Al-Ikhlas need an Android-based application to find the meaning of the Qur'anic verses to help and make it easier for students to find the meaning of the verses of the Qur'an and do the tasks given by Islamic Religion Teachers. Making the application's search for meaning verses of Qur'an using methods matching string (string matching) that is implemented in the search process said. String matching will perform the search process for a string or several strings found in a text or string. The algorithm used in string matching is berry ravindran, this algorithm has 2 phases, namely the preprocessing phase and the search phase. The phase preprocessing serves to create a shift value that will be used in the search phase. The value of the search phase is obtained from the rules of the algorithm. The Algorithm is berry ravindran implemented to perform analysis string matching in the application of finding the meaning of the verses of the Qur'an. This application to search for the meaning of the verses of the Qur'an can search for the meaning of the verses of the Qur'an by using voice, it is hoped that this voice search feature can facilitate the search for the meaning of the verses of the Qur'an. Speech recognition is implemented using one of the Google Cloud Platforms, namely the Google Speech API to detect spoken words when searching, so that it can make it easier for users to search for the meaning of the verses of the Qur'an. It is hoped that this application can be used as a source of knowledge and useful for grade 4-5 students at Elementary School Al-Ikhlas so that they are more diligent in reading the Qur'an and finding out the meaning of the verse, in order to guide them to the right path to the path that is pleasing to Allah.